Fatigue Strength Of Fixed Offshore Structures Under Variable Amplitude Loading Due To Wind, Wave, And Ice Action - Braun, Moritz (author); Dörner, Alfons (author); Willems, Tom (author); Seidel, Marc (author); Hendrikse, H. (author); Høyland, Knut V. (author); Fischer, Claas (author); Ehlers, Sören (author) (Volume 6: Polar and Arctic Sciences and Technology, 2022)
Fixed offshore wind turbines are increasingly developed for high latitude areas where not only wind and wave loads need to be considered, but also moving sea ice. Current structural design rules do not adequately consider the effect of ice loading on fatigue life, due to missing studies on fatigue strength of welded joints under combined wind, wave, and ice action. Thus, a methodology to determine combined variable-amplitude loading (VAL) spectra was developed in a previous study. The stress state time-history at an exemplarily selected point in the support structure of an offshore wind energy monopile was translated into a VAL sequence. This sequence is used as an input for fatigue tests of butt-welded joints in the current study. The current study presents the VAL spectrum and the corresponding VAL time series, the results of the fatigue tests and compares them to typical fatigue damage sums for other stress spectra. Green Open Access added to TU Delft Institutional Repository 'You share, we take care!' - Taverne project https://www.openaccess.nl/en/you-share-we-take-care Otherwise as indicated in the copyright section: the publisher is the copyright holder of this work and the author uses the Dutch legislation to make this work public. Offshore Engineering